Growth and Production of Chinese Kale (Brassica oleracea L.) on Different Growth Media and AB Mix Substitution with Organic Nutrition of Float Hydroponic Systems - Sinaga, Corry Dominika; Karno, Karno; Purbajanti, Endang (Journal of Tropical Crop Science and Technology, 2020)
This research aimed to assess the effect of several types of growing media and AB Mix substitution with organic nutrition on Kailan (Brassica oleraceae L.) growth. The study used a factorial 3 x 4 completely randomized design (CRD) with 3 replications. The first factor is the treatment of growing media which consists of Rockwool, Charcoal husk, and Cocopeat. The second is the AB Mix Substitution with organic nutrition consisting of AB Mix substitution with 0% organic nutrition, AB Mix Substitution with 25% organic nutrition, AB Mix Substitution with 50% organic nutrition, and AB Mix Substitution with 100% organic nutrition. Growth parameters observed included plant height, number of leaves, root length, canopy wet weight, root wet weight, canopy dry weight, root dry weight, and chlorophyll. Data were analyzed using ANOVA and continued by DMRT (Duncan's Multiple Range Test) at 5% level. The results showed that the planting media treatment increased growth in the plant height, number of leaves, root length, canopy wet weight, root wet weight, and canopy dry weight. The treatment of AB Mix substitution with 25% organic nutrition is equivalent to the treatment with 0% organic nutrition for all parameters except chlorophyll. The AB Mix substitution treatment with 50% organic nutrition is not equivalent to the treatment without substitution. The higher substitution treatment will affect growth.